UJI BEBERAPA KONSENTRASI CENDAWAN ENTOMOPATOGEN Cordyceps militarisL. FriesLOKAL UNTUK MENGENDALIKAN HAMA ULAT JENGKAL Chrysodeixis chalcites Esp. PADA TANAMAN KEDELAI (Glycine max L. Merrill) - Asmida Ayu; Desita Salbiah; Agus Sutikno (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Soybeanis a source of vegetable protein and the basis of variety of processed products. Chrysodeixis chalcites is one of the major pests in soybean plant. Currently efforts in controlling C. chalcitesstill use synthetic insecticide that can have negative impacts. Reducing the effects caused by synthetic insecticide, therefore need alternative in pest control techniques such as use local entomopathogenic fungi Cordyceps militaris. The purpose of this research is to get concentration of local entomopathogenic fungi C. militaris which best in control C. chalciteson soybean plants. Research prepared using completely randomized design (CRD) with 5 treatments and 5 replications. The treatment used is some concentration of local entomopathogenic fungi C. militaris consists of 5 treatments are 20 g/l of water (45,2 x 107 kon/ml), 30 g/l of water (67,8 x 107 kon/ml), 40 g/l of water (90,4 x 107 kon/ml), 50 g/l of water (113,0 x 107 kon/ml), and 60 g/l of water (135,6 x 107 kon/ml). The results showed concentration of local entomopathogenic fungi C. militaris 60 g/l of water (135,6 x 107 kon/ml) is the best concentration because can to provide the fastest time to early death for 45,4 hours, lethal time 50 (LT50) for 113,8hours, and caused total mortality 84% for 168 hours. The exact concentration to control 95% of the population of C. chalcites is 18,59% or 185,9 g/l of water. Keyword:Local entomopathogenic fungi Cordyceps militaris L. Fries,Chrysodeixis chalcitesEsp., andSoybean(Glycine max L. Merrill).